Microwave-assisted copper catalyzed decarboxylative reductive coupling of para-quinone methides with 3-indoleacetic acids: rapid access to polycyclic spiroindolequinone derivatives. Issue 6 (13th February 2023) - Song, Gui-Ting; Liu, Yuan; Hu, Xin-Yue; Li, Shu-Ting; Liu, Jian-Bo; Li, Yong; Qu, Chuan-Hua
Abstract : Indolylated diarylmethanes derived from microwave-assisted copper catalyzed decarboxylative reductive coupling of para -quinone methides with 3-indoleacetic acids make spiroindolequinones rapidly accessible. Abstract : The green synthesis of indolylated diarylmethanes via copper-catalyzed decarboxylative reductive coupling of para -quinone methides ( p -QMs) with 3-indoleacetic acids in radical reactions under microwave irradiation is described. The title compounds with diverse structures and medicinal value can be rapidly obtained under mild conditions with good to excellent yields (42 examples, up to 96% yield). The distinguishing features of this method include a very short reaction time, simple operation, mild reaction conditions, an inexpensive and green catalyst, high yields, scalability, and broad substrate scope. The synthetic value of this protocol was highlighted by the synthesis of polycyclic spiroindolequinones via oxidative dearomative spirocyclization. In addition, the mechanistic investigations offered an important insight into the reductive cross-coupling process between diarylmethyl radicals and indole-3-methyl radicals.